2015
DOI: 10.1080/15377857.2015.1039747
|View full text |Cite
|
Sign up to set email alerts
|

Credibility Enacted: Understanding the Meaning of Credible Political Leadership in the Dutch Parliamentary Election Campaign of 2010

Abstract: In times of perception politics, the credibility of electoral candidates is a crucial asset in political marketing. This raises the question to which political leaders citizens attribute credibility, and how political credibility is gained and lost through media performance.We analyze and compare two contrasting cases during the Dutch parliamentary election campaign of 2010. Whereas in this campaign Mark Rutte -leader of the liberal party VVD -gained credibility, the credibility of Job Cohen -at the time leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
(58 reference statements)
0
12
0
1
Order By: Relevance
“…Credible elections—that is to say, elections which reflect the free will of the people, inclusiveness, transparency, accountability and competitiveness (Van Weelden 2013 ; Van Zuydam and Hendriks 2018 )—are an important part of putting leaders in power (Lappin 2009 ; Abdullah 2019 ). Malawi held tripartite elections to choose members of parliament, local government councillors and a president in May 2019, where turnout was 74.44%.…”
Section: Introductionmentioning
confidence: 99%
“…Credible elections—that is to say, elections which reflect the free will of the people, inclusiveness, transparency, accountability and competitiveness (Van Weelden 2013 ; Van Zuydam and Hendriks 2018 )—are an important part of putting leaders in power (Lappin 2009 ; Abdullah 2019 ). Malawi held tripartite elections to choose members of parliament, local government councillors and a president in May 2019, where turnout was 74.44%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that leader credibility surfaced in peer-reviewed journals representing a wide range of disciplines: public administration (Grasse et al 2014 ; Gabris et al 2001 ), business strategy (Salicru and Chelliah 2014 ), economics (Komai and Stegeman 2010 ), business management (Chun et al 2014 ; Kouzes and Posner 2005 ), sports management (Swanson and Kent 2014 ), political science (Myerson 2008 ; Van Zuydam and Hendriks 2018 ), medical and health services (Davidhizar 2007 ; Loh et al 2016 ), education (Bolkan and Goodboy 2009 ; Holland 1997 ), and psychology (Sweeney et al 2009 ). Empirical research has explored relationships between leader credibility and various outcomes, such as leader self-awareness (Grasse et al 2014 ), subordinate burnout (Gabris and Ihrke 1996 ), managerial innovation (Gabris et al 1999 ), motivating language (Holmes and Parker 2017 ), subordinates’ perceived cost of seeking feedback (Chun et al 2014 ), and affective well-being at work (Rego and Pina e Cunha 2012 ).…”
Section: Introductionmentioning
confidence: 94%
“…Aristotle wrote that ethos had three parts: intelligence, moral virtue, goodwill towards audience Lafferty ( 2004 )* Hovland et al ( 1953 ) credibility elements: trustworthiness and expertise Simons et al ( 1970 ) Sue-Chan and Latham ( 2004 ) Kim et al ( 2009 )* FjałKowsKi ( 2014 ) Swanson and Kent ( 2014 )* Van Zuydam and Metze ( 2018 )* Van Zuydam and Hendriks ( 2018 )* Yin et al ( 2019 ) Andersen ( 1961 ) and Berlo et al ( 1969 ) Added dynamism to credibility elements of trustworthiness and expertise Although no articles in the SLR cited these researchers, they are credited with adding “dynamism” to the definition of leader credibility and are important to the historical context O’Keefe ( 1990 ) Elements: expertise and trustworthiness Kouzes and Posner ( 2005 )* Huffaker ( 2010 ) Men ( 2012 ) Norton et al ( 2014 ) Van Zuydam and Metze ( 2018 )* Van Zuydam and Hendriks ( 2018 )* Hackman and Johnson ( 1996 ) Elements: competence, trustworthiness, dynamism Russell and Stone ( 2002 )* Holmes ( 2016 ) McCroskey and Young ( 1981 ) McCroskey and Teven ( 1999 ) adapted source credibility to leader credibility and created a measure. Credibility Elements: trustworthiness, expertise, goodwill (perceived caring) Bolkan and Goodboy ( 2009 ) Basford et al ( 2014 ) Swanson and Kent ( …”
Section: Literature Analysis and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the entire online group, the primary influence of opinion leaders on a group has long been discussed in many contexts, such as in public management (e.g., studies on the key role of opinion leaders in controlling public opinion and improving government-public relationships) [42][43][44], marketing (e.g., studies on opinion leaders and word-of-mouth marketing) [18,[45][46][47], the media, and information dissemination (e.g., studies on opinion leader identification and classification) [48][49][50][51]. Switching to the knowledge-sharing domain, however, only a few scholars (e.g., Smith [18]) have recognized that opinion leaders have a remarkable capability to reflect the requirements of users or promote the development of organizations [52].…”
Section: Opinion Leadermentioning
confidence: 99%